Character recognition of Malaysian vehicle license plate with deep convolutional neural networks - How D.N.T.; Sahari K.S.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Classification (of information); Computer networks; Convolution; Intelligent control; Intelligent robots; License plates (automobile); Neural networks; Optical character recognition; Robotics; Smart sensors; Background image; Convolutional networks; Data augmentation; Deep convolutional neural networks; Learning models; Vehicle license; Vehicle license plate recognition; Vehicle license plates; Deep neural networks